Development and Application of Real-time Dynamic Flood Risk Mapping - TAN Senming; GUO Shuhui; CAO Runxiang (Renmin Zhujiang)
As an important non-engineering measure for flood control management, the static flood risk map has been widely applied in flood prevention efforts. With the rapid development of computer technology and information platforms, real-time, dynamic analysis has become a primary focus in flood risk mapping research. This paper reviews the development process and technical routes of flood risk mapping domestically and internationally, summarizing the recent advancements in real-time dynamic flood risk maps. Several key issues require further study to meet the practical application needs of flood control and drought management departments in areas such as flood risk prediction, engineering scheduling, disaster status inquiry, and personnel evacuation. These issues include improving the layout of hydrological stations, strengthening research on rainfall forecasting models, and coupling with hydrodynamic models to enhance flood forecast accuracy and extend flood forecast periods. In addition, improving high-precision terrain generalization, high-speed parallel computing, and artificial intelligence applications will increase model calculation efficiency. This framework aims to support decision-making in flood control and drainage planning, water conservancy project construction, and management of rivers, lakes, and reservoirs.